Can We Standardize Clinical Functional Neuroimaging Procedures? - Beisteiner, Roland; Pernet, Cyril; Stippich, Christoph (Frontiers in Neurology, 2019)
In recent years, the interest in clinical applications of functional neuroimaging techniques like functional Magnetic Resonance Imaging (fMRI) or modern Magneto- or Electro- Encephalography (MEG-EEG) has steadily grown as have discussions about possible standardizations of these methodologies. The modern techniques allow non-invasive localization of essential brain functions with the potential to extend or even replace invasive clinical technologies. The focus of this article is to discuss standardization options in using functional MRI for clinical cases, mostly in the context of medical decision aid for planning treatment (radiotherapy and surgery).